Hubungan Pengalaman Bertanding dan Kepercayaan Diri terhadap Kemampuan Receive Bola Voli - Dimas Sofi Setiawan; Erwin Nizar Priambodo; Wiga Nurlatifa Romadhoni; Mohammad Rizqi Okta Afandi (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to examine the relationship between competitive experience and self-confidence on receive ability in volleyball athletes of Porvit Kudus club. A quantitative correlational design with total  sampling was used, involving 14 respondents. Data were collected through a competitive experience questionnaire, a self-confidence scale, and match statistics for receive ability. Data analysis used Pearson correlation and multiple linear regression. The results showed no significant relationship between competitive experience and self-confidence on receive ability (p > 0.005), although a low positive correlation tendency was found. These findings indicate that receive ability is more influenced by technical and neuromotor factors. Therefore, structured and repetitive technical training is remommended to improve receive ability.